Aspectos geodinâmicos associados ao promontório de Jericoacoara, Ceará - Oliveira, Rafael Fialho de (2022)
The seaside of the Ceará state constitutes one of the most vulnerable systems to unplanned forms of use and occupation, whose most perceptible changes are the ones on the coastline, by erosion and accretion processes due to alterations in the processes of sediment transferring between beaches and sand dune fields. The setting of its coastline is decisive in the origin and evolution of coastal plain, with points and promontories being types of coast features that condition the associated geodynamic aspects. Thus, the production of studies that seek to better characterize the processes acting within these environments is important. Based on such premises, the general objective of this paper was to analyze the space-time evolution of the Jericoacoara Promontory between 1986 and 2021 via extraction of the coastlines and the associated active wind deposits (sand dune fields and sediments in movement on the active aspersion plain) based on Geoprocessing and Remote Sensing techniques aimed at coastal analysis, through qualitative and quantitative procedures and aided by on-site visits. To this end, we processed images previously selected from 8 OLI and Landsat 5 TM satellite, followed by the discussion and application of methods of temporal mapping of coastlines and active wind deposits – with delimitation via visual interpretation being the most appropriate for the first one and delimitation via Principal Component Analysis (PCA) and Supervised Classification Analysis (Maximum Likelihood) for the second one. Having obtained the space-time data, we processed them via Digital Shoreline Analysis System (DSAS) and the Change Polygon Method. Therefore, based on the LRR procedure, we verified that the coastline of the Jericoacoara Promontory is stable in three sectors (A, B and C), has a tendency towards progradation in one sector (D), and extreme progradation in Sector E, presenting statistically significant erosion in 32.79% of the mapped coast; and 44.68% of statistically significant progradation. The presented stability enabled the reinsertion of a considerable sediment extension (2,51 km2) to the coastal dynamic from the NE portion of the Promontory, migrated at a rate of 21.41 m/y (EPR procedure for sand dune fields). Regarding the tendency and extreme tendency towards progradation, it was evidenced by the sediment input, in the downstream beach strip, from the barcana dunes bypass in the NE-SW direction at a general average rate of 16.29 m/y. Thus, we conclude that the application of Geoprocessing and Remote Sensing techniques aimed at coastalanalysis, especially regarding mapping in multi-temporal scale, is an effective tool to understand the geodynamic aspects associated to points and promontories in Ceará, enhancing actions aimed at environmental monitoring, coastal management and territorial planning of environments vulnerable to soil use and occupation processes.